Isoniazid potentiates tigecycline to kill methicillin-resistant Staphylococcus aureus - Xuan-wei Chen; Hao-qing Chen; Jia-han Wu; Zhi-han Wang; Yu-Qing Zhou; Si-qi Tian; Bo Peng (Emerging Microbes and Infections, 2025)
Therapeutic option for treating methicillin-resistant Staphylococcus aureus (MRSA) infection is urgently required since its resistance to a broad spectrum of currently available antibiotics. Here, we report that isoniazid is able to potentiate the killing efficacy of tigecycline to MRSA. The combination of isoniazid and tigecycline reduces the minimal inhibitory concentration of clinic MRSA strains to tigecycline. The killing activity of tigecycline is further confirmed by killing experiments and murine infection model. We further demonstrate the mechanism that isoniazid increases intracellular accumulation of tigecycline by promoting the influx but limiting the efflux of tigecycline through proton motive force. We also show that isoniazid and tigecycline synergize to increase the abundance of isoniazid-NAD adduct, which in turn damage cell membrane, possibly contributing to the disruption of PMF. Whereas phosphatidylethanolamine and cardiolipin are able to abrogate the synergistic effect of isoniazid plus tigecycline. Thus our study provides a new perspective that antibiotics, e.g. isoniazid, once recognized only to target Mycobacterium tuberculosis, can be repurposed as antibiotic adjuvant to tigecycline, expanding our choice of antibiotic–antibiotic combinations in treating bacterial infectious diseases.